Ameliorating effect of Berberis lycium root bark extracts against cisplatin-induced nephropathy in rat - Anwar, Rukhsana; Sultan, Rabeea; Batool, Fasiha (Bangladesh Journal of Pharmacology, 2018)
The aim of this study was to investigate the sub-acute nephroprotective effect of Berberis lycium root bark extracts against cisplatin-induced nephrotoxicity. Aqueous and methanol extracts (200 and 400 mg/kg) were co-administered with cisplatin (4 mg/kg) for 19 days. Results showed that cisplatin significantly (ap<0.05) raised the serum creatinine, uric acid, urea level as well as tissue MDA level as compared to control group. It decreased GST activity, tGSH and catalase activity in rats. Both extracts significantly reduced the serum creatinine, urea and uric acid levels. Moreover, GST, CAT activity and tGSH content were significantly (p<0.05) increased and MDA level was decreased. Histopathological examination showed that both extracts efficiently reversed the morphological changes and damage induced by cisplatin. It is concluded that both extracts of B. lycium root bark possess nephroprotective effect against cisplatin-induced nephrotoxicity. Video Clip of Methodology: Histological study of rat kidney: 14 min 02 sec Click to watch